FEATURES OF COMPONENT INTERACTION IN LIQUID ALLOYS OF TERNARY Al-Ge-3d-Me (Me=Mn, Fe,Ni,Cu) SYSTEMS: DOI: https://doi.org/10.17721/1728-2209.2020.1(57).9 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
The features of the component interaction in liquid alloys of ternary Al-Ge-3d-Me systems (Me = Mn, Fe, Ni, Cu) are described. A joint analysis of the concentration dependences of the enthalpies of mixing of liquid alloys previously obtained by the authors via high-temperature calorimetry, and also of the phase diagrams of the constituent binary systems was carried out. The relationship between the enthalpy values and the type of short-range ordering in liquid alloys of the studied systems was established. The visual similarity of the topology of the projections of DmH isolines of the Al-Ge-Fe (Ni, Cu) liquid alloys and a completely different course of the isolines of the enthalpies of mixing for the liquid Al-Ge-Mn alloys are established. The changes in the absolute values of the DmHmin from system to system are observed. The enthalpies are approximately the same for the Al-Ge-Mn and Al-Ge-Fe systems (about -20 kJ×mol-1), they increase significantly from Al-Ge-Fe to Al-Ge-Ni (-50 kJ×mol-1), and then decrease substantially towards the Al-Ge-Cu system (-15 kJ×mol-1). For the Al-Ge-Mn (Fe, Ni, Cu) liquid alloys the lines of extreme interaction are located near the 3d-corner of the concentration triangle. These lines connect the compositions of the most stable intermetallic compounds in binary Al(Ge)-Mn(Fe, Ni, Cu) systems. It has been shown that the thermodynamic properties of Al-Ge-Fe (Ni, Cu) liquid alloys are mainly determined by the pair interaction of the components of the constituent binary Al-Fe(Ni, Cu) and Ge-Fe(Ni, Cu) systems, the influence of Al-Fe(Ni, Cu) systems being prevailed. For the Al-Ge-Mn system, the interaction of components in the Ge-Mn binary system gives the main contribution to the thermodynamic properties of the ternary system. The Al-Ge-Mn (Fe, Cu) systems are characterized by significantly lower absolute values of the heats of alloy formation compared to the Al-Ge-Ni one. The specified characteristics of component interaction in the ternary systems under consideration and different values of the enthalpies of mixing are determined by the peculiarities and regular changes of the electronic structure of 3d metals across the 3d series from Mn to Cu.
Keywords: aluminum, germanium, manganese, iron, nickel, copper, enthalpy of mixing.